Aplicación de la nicsp 39 en el registro y pago de remuneración del GAD municipal de Machala periodo 2022. - Cedeño Cantos, Nataly Liseth (Machala : Universidad Técnica de Machala, 2022)
The implementation of the International Public Sector Accounting Standard 39 (IPSAS 39) in the recording and payment of the remuneration of the Machala Municipal GAD presents deficiencies in the accounting treatment of the payment record of remunerations, in addition to the lack of knowledge and training of the personnel responsible for the accounting record of remuneration can cause errors in the record, interpretation and application of the National Governmental Standard, regulations or laws that take precedence over the principles and criteria established by IPSAS 39. The aim of this research is to apply the International Public Sector Accounting Standard 39 (IPSAS 39) in the recording and payment of remuneration of the Machala Municipal GAD during the 2022 period. The accounting record of remunerations following the guidelines established by the International Public Sector Accounting Standard 39 Employee Benefits, is an essential aspect of Government Accounting that guarantees transparency and financial responsibility in public management and facilitates long-term financial planning. The methodology used is applied research, which is based on viable and applicable solutions to concrete problems. The accounting record of the Payroll of the Machala Municipal GAD reveals that a correct accounting treatment of payments to workers under IPSAS 39, facilitates the users of financial information to better understand the economic situation and performance of an entity, as well as provides comparable and reliable information for accountability.
La aplicación de la Norma Internacional de Contabilidad del Sector Público 39 (NICSP 39) en el registro y pago de la remuneración del GAD Municipal de Machala presenta deficiencias en el tratamiento contable del registro de pago de remuneraciones, además la falta de conocimiento y capacitación del personal encargado del registro contable de la remuneración puede ocasionar errores en el registro, interpretación y aplicación de la Norma Gubernamental Nacional, reglamentos o leyes que se anteponen a los principios y criterios establecidos por la NICSP 39. El objetivo de esta investigación es aplicar la Norma Internacional de Contabilidad del Sector Público 39 (NICSP 39) en el registro y pago de remuneración del GAD Municipal de Machala durante el periodo 2022. El registro contable de las remuneraciones siguiendo los lineamientos estipulados por la Norma Internacional de Contabilidad del Sector Público 39 Beneficios a los Empleados, es un aspecto esencial de la Contabilidad Gubernamental que garantiza la transparencia y la responsabilidad financiera en la gestión pública y facilita la planificación financiera a largo plazo. La metodología utilizada es la investigación aplicada, la cual se basa en soluciones viables y aplicables a problemas concretos. El registro contable del Rol de Pago del GAD Municipal de Machala revela que un correcto tratamiento contable de los pagos a trabajadores bajo la NICSP 39, facilita a los usuarios de la información financiera a comprender mejor la situación económica y el desempeño de una entidad, así como proporciona información comparable y confiable para la rendición de cuentas.
Keywords: NICSP 39; REMUNERACIÓN; CONTABILIDAD GUBERNAMENTAL